Determinan Pembiayaan Mikro Pada Bank BRI Syariah - Sarah Khafidzah Salim (Faculty of Economics and Business, 2022)
This study aims to analyze the determinants of microfinance at Bank BRI Syariah in the short and long term. This study uses the Vector Error Correction Model (VECM) analysis method. The results of this study indicate that in the short term NPF, DPK, ROA, FDR have no significant effect because variables that are not significant in the short term indicate that a variable reacts to other variables takes time which generally occurs in the long term. Meanwhile, in the long term DPK, ROA, FDR, have a significant positive effect on Microfinance. NPF has a significant negative effect on Microfinance.